Atividade ansiolítica e antinociceptiva do óxido de linalol em modelos animais - Maior, Flávia Negromonte Souto (2011)
Linalool oxide (OXL) is a monoterpene, monocyclic alcohol, which has pleasant odor and can be found in essential oils of some aromatic plants. It can also be obtained from linalool by natural oxidation or synthetic processes. The lack of research on possible pharmacological activities of OXL encouraged this work that had as main objective the assessment of anxiolytic-like and antinociceptive-like activities of OXL on male Swiss mice. Initially was investigated the 50% lethal dose (LD50) of OXL in order to establish safe doses and concentrations for subsequent tests. The OXL was used in the experiments at doses of 50, 100 and 150 mg/kg, intraperitoneally (i.p.) and at concentrations of 0.65%, 1.25%, 2.5% and 5.0% by inhalation (INH). In order to investigate the profile of action of this monoterpene on central nervous system, general tests such as behavior pharmacological screening and rotarod test were performed. During the screening, analgesia was the main effect observed in animals treated with OXL i.p. or by INH route. Inhaled OXL also increases rearing and climbing behavior in animals. In rotarod test OXL i.p. or INH caused no motor impairments in mice. In specific tests, inhaled OXL presented a profile of anxiolytic drug by increasing the time spent in open arms of elevated plus maze and increasing the time spent in the brightly-lit chamber of the light/dark box. The standard drug used in these animal models of anxiety was diazepam. OXL i.p. showed a profile of antinociceptive drug, decreasing the number of abdominal writhing induced by acetic acid and decreasing the time spent by the animals licking the injected paw in both observation phases of the formalin test. In these tests, morphine was used as standard drug. Pharmacological tools such as naloxone, atropine, sulpiride and caffeine were used to attempt elucidate the mechanism involved in the antinociceptive effect of OXL. Sulpiride and naloxone reversed this antinociceptive effect in the first phase of the formalin test, and caffeine in both phases, suggesting the involvement of opioid, dopaminergic and adenosinic transmissions in the antinociceptive action. The development of this thesis has presented preliminary findings of OXL psychopharmacological activity. Further investigations with this monoterpene can lead to the future development of a new drug or molecule with greater potency and selectivity.